HUBUNGAN PENGETAHUAN DENGAN SIKAP PETUGAS KESEHATAN TENTANG TRIASE DI INSTALASI GAWAT DARURAT (IGD) RSU WIRADADI HUSADA BANYUMAS - Darsiti, Darsiti; safitri, Maya; Murniati, Murniati (SINERGI : Jurnal Riset Ilmiah, 2025)
The Emergency Department (ED) is a vital healthcare unit that requires rapid and accurate decision-making to ensure patient safety and deliver effective care. Triage, the process of prioritizing patients based on the severity of their conditions, is crucial in preventing overcrowding and optimizing resource allocation. The effectiveness of triage implementation is closely linked to the knowledge and attitudes of healthcare workers. This study aimed to examine the relationship between healthcare workers’ knowledge and attitudes regarding triage in the Emergency Department of RSU Wiradadi Husada Banyumas. A quantitative research design with a cross-sectional approach was employed. The study population included 27 healthcare workers assigned to the ED. Primary data were collected using a structured questionnaire assessing knowledge and attitudes toward triage. Data analysis was performed using the Spearman Rho correlation test. Results showed that most respondents demonstrated good knowledge (51.9%) and a positive attitude (92.6%) regarding triage. However, statistical analysis indicated no significant relationship between knowledge and attitudes, with a significance value of 0.176 (p > 0.05) and a correlation coefficient (r) of 0.268. These findings suggest that while knowledge and attitudes toward triage were generally high, knowledge alone may not be the determining factor influencing attitudes. Further research is recommended to explore other factors, such as training, clinical experience, and organizational support, that may contribute to the development of healthcare workers’ attitudes and competencies in triage implementation.